1996
DOI: 10.3109/01485019608987088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Motility Characteristics and Normal Sperm Morphology of Human Semen Samples Separated by Percoll Density Gradient Centrifugation

Abstract: The aim of this study was twofold: to investigate the ability of Percoll gradient centrifugation (52, 68, 84%) to fractionate semen samples according to motility quality and percentage normal morphology and to determine whether there is an association between sperm motility quality and percentage normal morphology. Sperm motility was evaluated using a Hamilton Thorn analyzer and normal sperm morphology was manually assessed according to the strict criteria (< or = 4, 5-14, and >14%). The majority of motility p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…These sperm motion variables , such as PM, VSL, VCL, YAP, and LIN, may serve as prognostic indicators for male infertility . Several researchers have reported the relationship of fertility potential and sperm motility parameters measured with CASA [5][6][7][8]. CASA results of the present study also showed that compared with the control group, VCL, VSL, VAP and BCF in asthenozoospermia group and oligospermia group were significantly decreased, which suggested that the impaired sperm motility may play an important role in male factor infertility .…”
Section: Discussionsupporting
confidence: 68%
“…These sperm motion variables , such as PM, VSL, VCL, YAP, and LIN, may serve as prognostic indicators for male infertility . Several researchers have reported the relationship of fertility potential and sperm motility parameters measured with CASA [5][6][7][8]. CASA results of the present study also showed that compared with the control group, VCL, VSL, VAP and BCF in asthenozoospermia group and oligospermia group were significantly decreased, which suggested that the impaired sperm motility may play an important role in male factor infertility .…”
Section: Discussionsupporting
confidence: 68%
“…Percoll TM gradient density (Kabi Pharmacia, Uppsala, Sweden) has been used effectively, and has been approved for sperm selection since 1988 [8][9][10][11] owing to its superior selection ability compared with simple washing or swim-up preparations [12][13][14][15]. However, several preparation media that use centrifugation gradients have been studied [8][9][10][11], including Isolate TM , SpermGrad TM , Sil-Select Plus TM , Optiprep TM and PureSperm  . Among them, PureSperm yielded similar sperm parameters to those of Percoll and could be considered a suitable substitute for Percoll, which was abandoned in 1996 owing to toxicity [16].…”
Section: Resultsmentioning
confidence: 99%
“…Percoll gradient density (Kabi Pharmacia, Uppsala, Sweden) has been used extensively for spermatozoa selection. Several studies have proved Percoll's effectiveness (Iizuka et al, 1988; Mathieu et al, 1988; Punjabi et al, 1990; Claassens et al, 1996) and its comparatively better selection compared with simple washing or swim‐up preparation (Berger et al, 1985; McClure et al, 1989; Bongso et al, 1993; Moohan and Lindsay, 1995). Good clinical pregnancy rates were obtained after Percoll migration (Pardo et al, 1988; Sato et al, 1990), higher compared with swim‐up preparation (Guérin et al, 1989).…”
mentioning
confidence: 99%